Alcohol-related harm in relation to demographic factors: a longitudinal analysis of South African university students - Chakabuda, Tatenda (Rhodes University, Faculty of Humanities, Department of Psychology)
Introduction: Substance abuse, particularly alcohol abuse, has been widely studied. Due to its nature as a legal substance, the negative effects of alcohol are seemingly undermined. However, studies over time have constantly shown that despite being legal, alcohol has detrimental effects that should not be ignored. The consequences of alcohol can be divided into two broad categories: short-term and long-term. Short-term effects include blackouts, poor decision-making, engaging in unsafe sexual practices, and vandalism. On the other end, long-term effects include physiological harm and declining neurocognitive capacity. These and many other forms of harm have been studied, mainly in diagnosed alcoholic populations. Overtime, the population of interest in terms of alcohol-related harm broadened and it increasingly became evident that university students are susceptible to alcohol-related harm and alcohol use disorders due to their drinking patterns. Student drinking patterns involving binge drinking, pre-drinking, and drinking games are common due to the fact that in university, young adults have less supervision and more freedom. University students are also in an environment where excessive alcohol use is normalised, which makes them prone to alcohol-harm. However, it is important to note that different demographics are predisposed to alcohol-harm differently. Gender, age, racial and socio-economic differences are some factors that have been proven to differentiate individuals' likelihood of experiencing alcohol-related harm. Unfortunately, the differences across these different demographics within a South African university population are yet to be adequately explored. A large percentage of existing literature on demographic differences in the experience of alcohol harm in university cohorts has been largely amongst Western student populations. Methods: The present longitudinal study aimed to rectify this research gap by providing an evidence-based outcome analysis of demographic differences in the experience of alcohol-related harm in a South African student population. Data were collected using the Alcohol Use Disorders Identification Test (AUDIT) over a three-year period (2015, 2016 & 2017) from the same Rhodes University student cohort. Demographic data in the form of age, race, gender, and socio-economic status was analysed to study alcohol-related harm. Results: Data indicated that male students did not significantly experience greater alcohol-related harm compared to female students (p > 0.05). Similarly, white students did not experience significantly more alcohol-related harm compared to non-white students (p > 0.05). Findings further indicated that younger students experienced significantly greater alcohol-related harm in comparison to older students (p < 0.05). Lastly, students from a higher socio-economic background did not experience significantly greater alcohol-induced harm when compared to those from a lower socioeconomic status background (p > 0.05). Conclusion: Differences by age could be related to early brain development being linked to greater risk-taking, resulting in greater alcohol-related harm. Moreover, the absence of guardians may place younger student populations at greater risk for unhealthy drinking patterns, which may result in alcohol-related harm. Findings from the study suggest a greater need for interventions to target younger student populations. Future studies should explore why younger students are at greater risk for alcohol-related harm and seek to develop interventions that are more effective for this population.
Keywords: College students Alcohol use -- South Africa; College students Social conditions; Alcoholism Age factors; Alcoholism Sex differences; Drinking of alcoholic beverages Social aspects -- South Africa; Alcohol Use Disorders Identification Test